2002
DOI: 10.1562/0031-8655(2002)075<0237:spofai>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Properties of Fluoroquinolone Antibiotics in Water–methanol and Water–acetonitrile Mixed Solvents¶

Abstract: The fluorescence properties of ofloxacin (OFL), norfloxacin (NOR) and flumequine (FLU) were studied in H2O-CH3OH and H2O-CH3CN mixed solvents because these solvents were thought to behave as a biological mimetic system. The emission spectra of OFL and NOR were very sensitive to the composition of the solvents. In the Lippert-Mataga analysis of the steady-state fluorescence data of OFL and NOR, clear reverse solvatochromism was exhibited in both mixed solvents. This observation can be explained by the twisted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 30 publications
3
40
0
Order By: Relevance
“…11,14 Among FQs, norfloxacin [1-ethyl-6-fluoro-1,4-dihydro-4-oxo-7-(1-piperazinyl)-3-quinolinecarboxylic acid, NF], first synthesized in 1980 by introducing a piperazine ring at the carbon-7 of quinolone, 21 is a hydrophobic broadspectrum antibacterial drug with a half-life of 3.0−4.5 h. 22 It shows higher antibacterial activity and a broader substrate scope due to the presence of the piperazinyl ring, compared with other members in the same drug family devoid of this ring. 23 However, it has been reported that NF is able to induce phototoxicity in animals and humans, 24 which was initially speculated to be mediated by photosensitization mediated by singlet oxygen but was recently revised to be the result of a defluorination reaction. Although the latter is an uncommon reaction for fluoroaromatics due to the fairly high dissociation energy of the carbon−fluorine bond (up to ∼120 kcal/ mol), 25,26 it has been established that heterolytic C−F bond cleavage is more efficient for the tautomeric form than for the cationic or anionic form in some molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11,14 Among FQs, norfloxacin [1-ethyl-6-fluoro-1,4-dihydro-4-oxo-7-(1-piperazinyl)-3-quinolinecarboxylic acid, NF], first synthesized in 1980 by introducing a piperazine ring at the carbon-7 of quinolone, 21 is a hydrophobic broadspectrum antibacterial drug with a half-life of 3.0−4.5 h. 22 It shows higher antibacterial activity and a broader substrate scope due to the presence of the piperazinyl ring, compared with other members in the same drug family devoid of this ring. 23 However, it has been reported that NF is able to induce phototoxicity in animals and humans, 24 which was initially speculated to be mediated by photosensitization mediated by singlet oxygen but was recently revised to be the result of a defluorination reaction. Although the latter is an uncommon reaction for fluoroaromatics due to the fairly high dissociation energy of the carbon−fluorine bond (up to ∼120 kcal/ mol), 25,26 it has been established that heterolytic C−F bond cleavage is more efficient for the tautomeric form than for the cationic or anionic form in some molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Contrary to the k nr , the k r value seldom exhibits any clear trend as a function of solvatochromic parameter of mixed solvents because the change in k r in various solvent compositions is irregular. This phenomenon may be caused by the fact that the quantum yield of morin is very sensitive to the solvatochromic parameter of solvents, and CH 3 CN–H 2 O mixtures exhibit preferential solvation and microheterogeneity . Therefore, the ln(k r ) vs π * and ln(k r ) vs α plots measured at different excitation and emission wavelength do not exhibit any great differences.…”
Section: Resultsmentioning
confidence: 99%
“…Solubility of morin in CH 3 CN is much greater than that in H 2 O. Because CH 3 CN and H 2 O have quite different solvatochromic properties, contrary to the CH 3 OH–H 2 O mixtures, CH 3 CN–H 2 O mixed solvents show a wide diversity of features and behavior according to the composition . In CH 3 CN–H 2 O mixtures, three different kinds of mixtures can be distinguished, although boundaries of these mixtures are not sharp.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations